2008
DOI: 10.1016/j.visres.2008.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for a target against a 1/fβ continuous textured background

Abstract: We present synthetic surface textures as a novel class of stimuli for use in visual search experiments. Surface textures have certain advantages over both the arrays of abstract discrete items commonly used in search studies and photographs of natural scenes. In this study we investigate how changing the properties of the surface and target influence the difficulty of a search task. We present a comparison with Itti and Koch's saliency model and find that it fails to model human behaviour on these surfaces. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…(2006a) from situations in which there are no distractor objects and observers search for a discontinuity in a textured background (Clarke, Green, Chantler, & Emrith, 2008).…”
Section: University Of Illinois At Urbana-champaign Champaign Illinoismentioning
confidence: 99%
“…(2006a) from situations in which there are no distractor objects and observers search for a discontinuity in a textured background (Clarke, Green, Chantler, & Emrith, 2008).…”
Section: University Of Illinois At Urbana-champaign Champaign Illinoismentioning
confidence: 99%
“…Previous work on modeling visual search can be divided into two classes: search among sets of search items; and search in more naturalistic, continuous stimuli (typically photographs). The search task we consider in this study is that of a single target on a textured surface (Clarke, Green, Chantler, & Emrith, 2008). These stimuli have several advantageous properties: they offer a more naturalistic search task than sets of abstract geometric items; yet they are also fully parameterized and created pseudo-randomly so we can create many trials of equivalent difficulty, something that is difficult to do with photographic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…al. [Clarke et al, 2008] [Padilla et al, 2008] [Clarke et al, 2009] showed that the higher the level of background texture noise of a scene, the higher the level of difficulty of the search task. They represented the background surface as a height map by parameterizing an isotropic and random-phase noise 1/f β (being "β" the frequency roll-off magnitude factor of the inverse discrete Fourier transform of the height map and "σ RM S " the deviation of the roughness noise height).…”
Section: # Of Stimulimentioning
confidence: 99%